Agricultural Associations in India: A Study - Singh, K. P.; Gulati, Dipti (DESIDOC Journal of Library & Information Technology, 2011)
Agriculture is a vital component to the Indian economy and is necessary to all our daily needs. Theprofessional associations are committed to accelerate the growth and development of agricultural education,research and extension in the country. The present study explores the quantitative and qualitative growth ofthe agricultural associations in India and their nomenclature. Study also highlights the various activities undertakenby the agricultural associations in promotion of agricultural publications, organisation of conferences/seminars,fellowships/scholarships/awards. A list of agricultural associations in the country is also provided. doi: 10.14429/djlit.32.2.1405